2015
DOI: 10.1088/0004-6256/150/4/116
|View full text |Cite
|
Sign up to set email alerts
|

A Stellar Tidal Stream Around the Whale Galaxy, NGC 4631

Abstract: We report the discovery of a giant stellar tidal stream in the halo of NGC 4631, a nearby edge-on spiral galaxy interacting with the spiral NGC 4656, in deep images taken with a 40 cm aperture robotic telescope. The stream has two components: a bridge-like feature extending between NGC 4631 and NGC 4656 (stream SE ) and an overdensity with extended features on the opposite side of the NGC 4631 disk (stream NW ). Together, these features extend more than 85 kpc in projection. The orientation of stream SE relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 56 publications
9
40
0
1
Order By: Relevance
“…This is in good agreement with a total initial stellar mass (5.4 × 10 8 M ⊙ ) of the progenitor presumed in the N -body simulation of Martínez-Delgado et al (2015). However, red/metal-rich ends of these MDFs suffer from incompleteness even if we carefully construct them by considering completeness function derived in Section 2.3.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 82%
See 2 more Smart Citations
“…This is in good agreement with a total initial stellar mass (5.4 × 10 8 M ⊙ ) of the progenitor presumed in the N -body simulation of Martínez-Delgado et al (2015). However, red/metal-rich ends of these MDFs suffer from incompleteness even if we carefully construct them by considering completeness function derived in Section 2.3.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 82%
“…Furthermore, the lack of young stellar populations in Stream SE and NW is consistent with spatial consistent with lack of spatial correlation between these streams and the H I distribution discussed in Martínez-Delgado et al (2015). In the subsequent sections, we investigate the photometric properties of these two stellar streams based on the resolved stellar population.…”
Section: Spatial Density Distributionssupporting
confidence: 64%
See 1 more Smart Citation
“…Stars from the earliest events in hierarchical assembly should be found throughout the Galaxy (e.g., Brook et al 2007;Tumlinson 2010), while stars from later accretion of lower-mass galaxies mainly orbit in the outer halo, where streams of debris are long-lived thanks to long dynamical timescales. Indeed, the spatial coherence of merger debris can be observed in deep imaging of many galaxies (e.g., Malin & Carter 1980;Martínez-Delgado et al 2015) and kinematic coherence has been identified through spectroscopic studies in the Milky Way (e.g., Schlaufman et al 2009) and M31 (e.g., Gilbert et al 2009). Minor mergers clearly play a crucial role in assembling the outer halo, with its high degree of substructure and small or negative net rotation (e.g., Font et al 2011;Deason et al 2012;Pillepich et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Astronomical Journal, 152:72 (11pp), 2016 September doi:10.3847/0004-6256/152/3/72 in Martínez-Delgado et al 2015), Martínez-Delgado et al (2008) were not able to measure colors in the stream. Martínez-Delgado et al (2008) also produced a simple N-body model that mimicked the observed loopy stellar stream as a fossil of the tidal disruption of a single satellite in a merger event (total mass ratio of 1:4000), rejecting the hypothesis of multiple merger events in the halo of NGC 5907.…”
Section: Introductionmentioning
confidence: 99%